Using iron profiles to identify anemia of chronic disease in anemic children with tuberculosis - Reni Wigati; Endang Windiastuti; Badriul Hegar (Indonesian Pediatric Society, 2011)
Background Anemia of chronic disease (ACD) is commonly found in patients with chronic inflammation or infection. By examining soluble transferrin receptor or bone marrow iron, ACD was found in 80% of anemic adult tuberculosis (TB) patients. Iron profile, another tool to differentiate ACD from iron deficiency anemia (IDA), is both less expensive and less invasive. Few studies have been reported on iron profiles of anemic children with TB in Indonesia.Objective We aimed to use iron profiles to determine the proportion of ACD in anemic children with tuberculosis.Methods A cross-sectional study on anemic children with TB who came to Cipto Mangunkusumo Hospital and Tebet Puskesmas (community health center) was performed in September-November 2010. Iron profiles included the measurements of serum iron (SI), total iron binding capacity (TIBC), transferrin saturation (TF), and serum ferritin (SF).Results Our study comprised of 66 subjects, with a median age of 3.8 years (6 months–18 years). Most subjects had normal SI (85%), normal TIBC (71%), low transferrin saturation (51%), and normal SF (71%). Only 10 children had iron homeostasis disorder and 6 of these were diagnosed as having ACD. Thus, iron profiles failed to prove that iron metabolism was disturbed. The profile of children with organ-specific TB was more consistent with ACD compared to the profile of childhood TB. [SI 29.1 (11-83) vs 44 (10-151) μg/dL; TIBC 239.3 (100.80) vs 299.0 (58.51) μg/dL; TF 18.3 (4-100) vs 15 (1-53) %; and SF 154 (34.9-655) vs 36.1 (2.5-213.4) μg/L].Conclusion The proportion of ACD (9%) diagnosed by using iron profiles was not as high as previously reported. Further research using newer techniques is needed to detect ACD in anemic children with TB. [